Self-organization of the tribosystem under non-stationary conditions of friction from the standpoint of deformation-wave representations - Yu.O. Malinovskiy; O. A. Ilina; D.P. Vlasenkov; S.Yu. Oliinyk; O. O. Mikosianchyk (Проблеми трибології)
Mechanisms of structural adaptation of contact surfaces and lubricating materials during friction with the dominance of deformation processes in tribocontact have been  analyzed. The purpose of the work was to model the elastic-plastic properties of dissipative structures taking into account the anisotropic properties of the surface layers of the friction pairs and the boundary layers of the lubricating material. The modeling took into account the structural state of the latter formed due to heating and saturation with wear products, along with the physical and mechanical interaction of this layer with the outer surface of the part. An algorithm for determining the distributed tangent force along the length of the boundary layer of the lubricating material adjacent to the part has been developed based on the hypothesis of the wave-like state of the surface layer of the lubricating material on an absolutely flat (non-deformed) rough surface. Herein, under the action of tangent forces, the strip of lubricant is subject to horizontal compression and transverse movement. The distributed tangent stress along the length of the adjacency of the layer of densified lubricant to the part causes micro-slipping of the layer. Amplitude horizontal displacements of the boundary of the lubricant layer are determined when the beam-film is loaded with longitudinal stresses, which leads to partial disorientation of the film and loss of its originally rectilinear structured form, the transition of the lubricant layer to the state of the wave surface of a sinusoid shape. Also, a procedure for calculation of tangent forces causing the loss of elastic stability of the lubricant boundary layers resulting in the direct mechanical destruction of the lubricant boundary layer in the slipping zone of the contact surface is proposed based on  the elastic-frictional interaction of this layer with the near-surface layer of the metal